PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV SDN REJOSARI 01 - Kurnia Sari Ningrum; Fenny Roshayanti; Endang Wuryandini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The research aims of this study were to determine the effect of the PBL (Problem-Based Learning) learning model on the learning outcomes of flat-shape mathematics in class IV A students at SD Negeri Rejosari 01. This study used a pre-experimental research type, namely one group pretest-posttest design. The population of this study were all students in class IV A in SDN Rejosari 01 Semarang and used for saturated sampling. The data used are tested and documentation. The results showed that the average pretest score was 52.3 and the posttest average score was 83.4, meaning that student learning outcomes had increased, the average gain test was 69.39 which included the criteria for being quite effective, and the results of the paired sample test show 0.000 <0.05 then H0 is rejected and Ha is accepted. So it can be concluded that there is an influence of the PBL learning model on the mathematics learning outcomes of class IV students at SDN Rejosari 01 Semarang.